SPECIFIC EFFECT OF LIMITING NUTRIENT ON PHYSIOLOGICAL EVENTS DURING CULTURE GROWTH - Ecker, R. E. (1961)
Ecker, R. E. (Iowa State University, Ames), and W. R. Lockhart. Specific effect of limiting nutrient on physiological events during culture growth. J. Bacteriol. 82:511–516. 1961.—In cultures of Escherichia coli strain K12, the sequence of physiological events at the time of growth cessation in populations limited by availability of carbon source (glucose), nitrogen source (ammonium sulfate), and oxygen was observed to differ in several respects. These included differences in the relationship between mass synthesis and cell division, the utilization of nonlimiting nutrients, and the nature of changes in energy metabolism. These observations are discussed with reference to problems involved in the experimental control of variables in growth studies.